Surgically Assisted Maxillary Expansion and Orthognathic Surgery in the Treatment of Hypoplastic Maxilla: An Ortho-Surgical Case Report - Rocha, Camila Lopes; Carvalho, Francisco Samuel Rodrigues; Souza, Maykel Sullyvan Marinho de; Hyppolito, João Octávio Pompeu; Silveira, Marcelo Leite Machado da; Alencar, Ana Beatriz Nobre de; Evangelista, Ícaro Girão (Brazilian Journal of Case Reports, 2025)
Skeletal Class III malocclusion, when associated with a moderate to severe discrepancy, compromises not only occlusal and masticatory function but also facial aesthetics, often resulting in a concave profile. In such cases, orthognathic surgery is the treatment of choice. In addition to the maxillary deficiency in the anteroposterior direction, transverse impairment is also common, leading to unilateral or bilateral posterior crossbite. In adult patients, due to skeletal maturation and ossification of the midpalatal suture, Surgically Assisted Rapid Maxillary Expansion (SARME) becomes an effective and indicated alternative. This paper aims to report the clinical case of a young female patient with Class III dentoskeletal deformity associated with maxillary atresia, treated through an orthodontic-surgical approach involving SARME followed by orthognathic surgery. Despite the complexity of the treatment, which included two surgical procedures, it was completed in 20 months—shorter than the average time reported in the literature. This outcome is attributed to the patient’s high adherence to treatment and the coordinated effort of a multidisciplinary team.